Web-oriented information and analytical system for improving complex of radiation protection of population and environmental objects at various regional levels - Журавков Vladislav; Germenchuk, Mariya; Tonkonogov, Boris; Tsybulka, Mikalai (Journal of the Belarusian State University. Ecology, 2025)
The paper considers the architecture, functionality and data model of a Web-based information and analytical system for improving the complex of radiation protection of the population and environmental objects at different regional levels. The object of the study is the methods, algorithms and technologies for constructing the architecture and optimized relational structure (model) of data consisting of tables that include fields for storing parameters and information about objects and resource potential, a public information and analytical system for a comprehensive study of the influence of anthropogenic and natural factors at various regional levels. The purpose of the work is to develop the architecture of the information and analytical system and the optimized relational structure (model) of data consisting of tables that include fields for storing parameters and information about objects and resource potential, and to determine the specialized software used in the development of the information and analytical system, including radioecological risks. Development of the architecture of the information and analytical system: definition of the general architectural style and main architectural solutions; definition and organization of the set of elements and components; definition of the functionality of the software modules of the system; description of the main roles and characteristics of the structural elements and possible types of interactions among them (interfaces); compliance with modular decomposition; endowment with the properties of flexibility, scalability and openness for expansion and implementation of additional functionality. Development of the data structure: definition of the purpose and content of tables; definition of table fields and their types; definition of relationships among tables; implementation of functional database objects that ensure modularity, scalability and portability. Definition of specialized software used in the development of the information and analytical system: selection of an integrated development environment, database management system and software tools (platforms, frameworks and libraries) that allow performing the assigned design and software implementation tasks; design of a prototype Web-platform for presenting environmental data using modern tools of geographic information systems; implementation of conditions for the creation of a pilot project of an applied Web-oriented information and analytical system.